Is Dry Needling Effective When Combined with Other Therapies for Myofascial Trigger Points Associated with Neck Pain Symptoms? A Systematic Review and Meta-Analysis - César Fernández-De-Las-Peñas; Gustavo Plaza-Manzano; Jorge Sanchez-Infante; Guido F Gómez-Chiguano; Joshua A Cleland; José L. Arias-Buría; Ibai López-de-Uralde-Villanueva; Marcos J. Navarro-Santana (Pain Research and Management)
Objective. To evaluate the effects of combining dry needling with other physical therapy interventions versus the application of the other interventions or dry needling alone applied over trigger points (TrPs) associated to neck pain. Databases and Data Treatment. Electronic databases were searched for randomized controlled trials where at least one group received dry needling combined with other interventions for TrPs associated with neck pain. Outcomes included pain intensity, pain-related disability, pressure pain thresholds, and cervical range of motion. The risk of bias (RoB) was assessed using the Cochrane risk of bias tool, methodological quality was assessed with PEDro score, and the quality of evidence was assessed by using the GRADE approach. Between-groups mean differences (MD) and standardized mean difference (SMD) were calculated. Results. Eight trials were included. Dry needling combined with other interventions reduced pain intensity at short-term (SMD −1.46, 95% CI −2.25 to −0.67) and midterm (SMD −0.38, 95% CI −0.74 to −0.03) but not immediately after or at long-term compared with the other interventions alone. A small effect on pain-related disability was observed at short-term (SMD −0.45, 95% CI −0.87 to −0.03) but not at midterm or long-term. The inclusion of dry needling was also effective for improving pressure pain thresholds only at short-term (MD 112.02 kPa, 95% CI 27.99 to 196.06). No significant effects on cervical range of motion or pain catastrophism were observed. Conclusion. Low-to-moderate evidence suggests a positive effect to the combination of dry needling with other interventions for improving pain intensity, pain-related disability, pressure pain thresholds, and cervical range of motion in people with neck pain associated with TrPs at short-term. No midterm or long-term effects were observed.